W Modification of Nickel-Rich Ternary Cathode Material for Efficient Lithium-Ion Batteries. Issue 1 (1st January 2023) - Song, Jinshang; Zhu, Lingzhi; Li, Yudong; Han, Enshan; Zhang, Qi; Chen, Gaojun; Zhang, Ziqiang; Yang, Xiaohui; He, Yanzhen
Abstract : As one of the fastest-growing cathode materials, Nickel-rich layered cathode material has caused much attention in the "next-generation" Li-ion batteries (LIBs) owning to the high specific energy, high operating potential and long cycling life. However, it still encounters a great of complications to realize the improvement of poor cycle stability and structural defects. In an effort to emphatically investigate the obvious advantages of eco-friendly and low-cost W doping cathode material on the crystalline morphology and electrochemical properties, LiNi0.65−x Co0.15 Mn0.20 Wx O2 (x = 0.5%, 1.0%, 2.0%) were synthesized by hydroxide coprecipitation and calcination crystallization method. Especially, when the amount of W is 1.0% molar ratio, the initial discharge capacity reaches 216.55 mAh g −1 and achieves a capacity retention of 95.95% after 100 cycles with the operation voltage of 2.7–4.4 V at 1C. The reliable results show that the primary particle size via doping appropriate content of W become significantly smaller which can effectively consolidate the stability of the crystal cathode material and improve the recycling performance evidently. In addition, the element of W was detected in the lattice of the crystal particle, which bring about somewhat increase of lattice spacing and expands the Li + diffusion channels during charge/discharge cycles. This work provides a potential application prospect by the strategy of W modification in the cathode materials of micron-sized particles for efficient lithium-ion batteries.